2009
DOI: 10.1007/s10554-009-9549-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute improvement of cardiac efficiency measured by 11C-acetate PET after cardiac resynchronization therapy and clinical outcome

Abstract: The purpose of this study was to examine the usefulness of (11)C-acetate positron emission tomography (PET) for assessing the efficacy of cardiac resynchronization therapy (CRT). Enrolled in this study were 20 patients with severe heart failure. All patients underwent 11C-acetate PET within 1 week after CRT. The oxygen consumption was measured by the monoexponential clearance rate of 11C-acetate (K(mono)) for both CRT-off and -on. Cardiac efficiency (CE) was determined using the concept of the work metabolic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Several PET studies in chronic CRT patients have shown that CRT improves oxygen metabolism and cardiac efficiency [28]. Kitaizumi et al now evaluated 20 patients very early (1 week) after CRT [29]. All patients underwent 11C-acetate PET and oxygen consumption was measured by the mono-exponential clearance rate of 11C-acetate (Kmono), while the biventricular pacemaker was off and then on.…”
Section: Nuclear Cardiologymentioning
confidence: 99%
“…Several PET studies in chronic CRT patients have shown that CRT improves oxygen metabolism and cardiac efficiency [28]. Kitaizumi et al now evaluated 20 patients very early (1 week) after CRT [29]. All patients underwent 11C-acetate PET and oxygen consumption was measured by the mono-exponential clearance rate of 11C-acetate (Kmono), while the biventricular pacemaker was off and then on.…”
Section: Nuclear Cardiologymentioning
confidence: 99%
“…This contributes to reverse remodelling of the ventricles and supresses the asymmetry in hypertrophy resulting from LBBB [32] . Some studies have shown that CRT can even reduce the global energy cost of heart activity [25,33] . Importantly, heart failure and CRT induce subcellular changes affecting energy management.…”
Section: Impact Upon Oxygen Consumptionmentioning
confidence: 99%
“…The native T1 values of myocardial tissues vary with myocardial extracellular water (edema), focal or diffuse fibrosis, fat, iron, and amyloid proteins. Meanwhile, quantitative parameters measured from 11C-acetate positron emission tomography (PET) imaging, such as Kmono and K1, have been largely utilized to characterize myocardial metabolism in heart diseases [11][12][13][14]. Kmono is considered as a robust marker for evaluation of myocardial oxygen consumption (MVO 2 ), while K1 is correlated with myocardial blood flow (MBF) in absolute terms.…”
Section: Introductionmentioning
confidence: 99%